Relationship of Changes in Central Lampung Economic Structure (Second Decade) Post Reform and Labor and Its Impilcity Toward Community Welfare - Erna Ermawati Chotim (International Journal of Science and Society, 2020)
Indonesia's financial situation is still less balanced between economic structure changes and labor absorption between sectors. Furthermore, it will have an impact on the welfare of the people in Indonesia. This study aims to 1) analyze the effect of changes in the economic structure on the structure of labor absorption and the welfare of the people in Indonesia, 2) to examine the impact of changes in the form of labor absorption on the interest of the people in Indonesia, and 3) to analyze the effect of changes in the economic system on labor absorption structures. Work in Indonesia. This study uses secondary data from Central Lampung Province and time-series data, namely the years 2012-2020. The results showed that the economic structure's variable changes had a negative and significant effect on the form of employment in Central Lampung. Changes in the financial system have no significant impact on the welfare of the people in Indonesia. The structure of work has a positive and significant effect on the people's welfare in Central Lampung. Changes in the economic system have an indirect and consequential negative impact on society's interest through Central Lampung's employment structure.